Strategi dalam Meminimalisir Pembelajaran Kanji (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2026)
Kanji learning is a major obstacle for Japanese language students, primarily due to the cultural differences and lack of knowledge of Chinese and Japanese characters. This obstacle limits students in learning Japanese, causing negative emotions in learning Kanji. In this study, the main focus is how to minimize strategies for learning kanji, what factors influence this learning process and how students overcome them. This study uses a literature study approach, also often referred to as library research, which is a method for collecting data and information through reviewing written sources, such as scientific journal articles, guidebooks, dictionaries, and other reliable materials in print or electronic formats that are directly related to the research topic. From the results of the study, students' strategies in the process of learning kanji are not easy, there are many obstacles in learning, even the use of electronic dictionaries and Kanji learning applications have a negative impact, because they make students rarely practice manual writing, which ultimately slows down mastery. The obstacles faced by students are divided into four main categories in Japanese, namely speaking obstacles such as choon, sokuon, tan-on, dialect, and intonation, listening obstacles such as sokuon, tan-on, speaking speed, dialect, intonation, obstacles in writing Kanji strokes, remembering shapes, neatness of writing, writing habits, and writing katakana and hiragana, and reading obstacles such as understanding Kanji, how to read onyomi-kunyomi, kango-jyukugo, reading long texts, and formal and informal texts.